Peran Kepemimpinan Ketua Sekaa Teruna Eka Bhakti Banjar Basang Tamiang dalam Mengelola Organisasi - Ida Bagus Dwira Adnyana; Ni Ketut Artini (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study examines the leadership performance of the Chairperson of Sekaa Teruna Eka Bhakti in responding to declining youth participation and organizational challenges triggered by modernization in Banjar Basang Tamiang, Desa Adat Kapal, Bali. The research aims to explain how leadership practicesparticularly in decision-making, communication, conflict management, and adaptationcontribute to the effectiveness and continuity of a traditional youth organization. Using a qualitative descriptive approach, data were collected through passive observation, semi-structured interviews with seven purposively selected informants, and documentation of organizational activities. The data were analyzed through an interactive model involving data reduction, display, and verification. The findings show that the chairperson applies a leadership style that balances structured planning with flexible responses to situational needs. Decisions are formulated through participatory discussions, supported by clear communication and accountability. Conflict is addressed through dialogue, while technology is used to strengthen coordination and information flow. This leadership approach encourages member involvement, maintains organizational cohesion, and helps the community navigate cultural shifts. Overall, the study highlights that effective leadership in community-based youth organizations requires a combination of cultural grounding and adaptive management to sustain relevance amid social change.